Subsurface users enterprises and contests for the election of the mayor - Kovin, V.S.; Panov, P.V.; Petrova, R.I. (Perm Federal Research Centre Journal, 2020)
The article continues the publication cycle concerning political processes in the cities of the Urals (Perm Krai, Sverdlovsk and Chelyabinsk Oblasts). The activities of city-forming enterprises in those cities are directly related to the subsurface users plants (extractive industry). The analysis of the elective contests of the city mayor shows that the cities where sufficiently large subsurface users enterprises are located have their own specific features. In general, these cities are more actively involved in urban politics, more often put forward their representatives to the position of mayor, consolidating the city elite around themselves. At the same time, these cities meet general requirements trends of urban politics in the industrial cities of the Urals. The activity of the subsurface users enterprises depends on the structure of the city’s economy, the economic status of an enterprise, as well as the degree of its independence and the interest of enterprise management in urban politics.